Cell Signalling (IntechOpen, 2023)
Intracellular signal transduction is an important topic of research in cell and molecular biology. It has a wide range of implications in growth, differentiation, development, animal polarity, cellular response monitoring, and many disease processes, including cancer. The functional homeostasis of a cell is assumed to be maintained by an intricate network of signaling that evolved through natural selection. This book includes chapters written in the frontier areas of research on cell signaling. Issues such as information thermodynamics, master regulation of immune tolerance, genetically encoded reporter circuits and their applications, hypoxia, and vitamin K2 mediated signaling processes are addressed and discussed by eminent researchers of the field.